Thoracic duct cyst of posterior mediastinum: a “challenging” differential diagnosis - Electra, Michalopoulou-Manoloutsiou (Ann Transl Med, 2016)
Thoracic duct cysts of the mediastinum are extremely rare entities and their pathogenesis still remains unknown. Imaging methods are not specific and show a cystic mass, however the real nature of the lesion is confirmed only with the help of histopathological examination after surgical excision. Here, we present a case of thoracic cyst in a 28-year-old female, lining in posterior lower mediastinum. The cyst was removed by video-assisted thoracic surgery (VATS) and the histopathological findings were that of thoracic duct cyst. Through this case, we propose an ideal surgical approach and diagnostic procedure.